(untitled) (Global Journal of Science Frontier Research, 2021)
As the climate turns cold and winter approaches, the global proliferation of novel coronavirus-19 is entering a new stage. The hallmark of this stage is that the mutant novel coronavirus has become a new driving force for the spread of viruses. This is a major new global challenge now. "God said, listen to Chen Yan, let justice back to the world, let human beings liberated from the novel coronavirus!"